Comparative Study on the Treatment Effect of Stretching and High-frequency Diathermy in Subjects With Gastrocnemius Tightness - Beom-Seop Kim; Yixin Wang; Ye-Jin Kim; Min-Young Kim; Hye-Seon Jeon (Physical Therapy Korea)
Background: Ankle flexibility is important for maintaining proper biomechanical function. Static stretching is used to improve flexibility with minimal risk; however, its effects are often temporary. Transfer of energy capacitive and resistive (TECAR) therapy has the potential to enhance muscle flexibility and circulation through deep heat applications. However, comparative studies evaluating the effectiveness of TECAR therapy and static stretching are lacking. Objects: This study aimed to compare the effects of static stretching therapy (ST) and combined TECAR and static stretching therapy (T-ST) in subjects with gastrocnemius muscle (GCM) tightness. Methods: Twenty-seven participants with bilateral GCM tightness were enrolled. To administer the ST and T-ST, which were each applied to both legs, the participants stood for 15 minutes on a wedge with a 0°–15° incline, with both feet on the wedge during ST and with TECAR therapy in resistive energy transfer mode applied to only one side of the GCM during T-ST. Muscle stiffness (MyotonPRO), dorsiflexion range of motion (DF-ROM), peak torque, and pennation angle (PA) of the GCM were measured before and after the intervention. Normality was confirmed using the Shapiro–Wilk test. Differences between the ST and T-ST leg conditions and between pre- and post-intervention changes in the legs were analyzed using paired t-tests. Results: There were no significant differences in any of the measured variables between the legs before the intervention. ST and T-ST legs showed significant improvements in all measured variables after the intervention (p < 0.05). T-ST legs demonstrated a significantly greater increase in DF and a greater decrease in PA than ST legs (p < 0.05). Conclusion: T-ST outperformed ST in reducing PA and increasing DF-ROM by promoting deep tissue relaxation and stimulating metabolic activity. This may lead to reduced pain and greater flexibility compared to ST. Maintaining an optimal PA ensures efficient force transmission during exercise, as evidenced by the observed increase in peak torque.